Sudut Pandang Aliran HumanistikTerhadap Model Pendidikan Andragogi - Bayu, Bayu (Universitas Prof. Dr. Moestopo (Beragama), 2004)
In -general there are two understand that teaching pedagogy that is valid and andragogy . Andragogy understand is the place to study participants as